TECHNOLOGY OF EFFICIENT PRODUCTION OF BREWERY BARLEY (INNOVATIVE ECONOMY, 2021)
Kuzina V.Yu. TECHNOLOGY OF EFFICIENT PRODUCTION OF BREWERY BARLEYPurpose. The aim of the article is a consolidated analysis of brewing barley cultivation practice in comparison with data of specialized malt laboratories on annual grain quality, with the intention to optimize elements of its cultivation technology adapted to changes in the environment, resource opportunities and modernized requirements for brewing grain quality.Methodology of research. The following methods were used in the study: monographic, scientific generalization (to determine the problems of production of malting barley), dialectical (in determining the impact on grain quality of natural and anthropogenic factors), system analysis, abstract and logical (in the analysis of operational information on production technology and statistics of cost structure, substantiation of conclusions and proposals).Findings. The technology of growing malting barley in farms of different levels of resource provision of the central and north-eastern regions of Ukraine is analysed and compared with the results of monitoring the quality of grain yield, which allows to make reasonable conclusions about the effectiveness of each of its elements. It is established that the adaptation of domestic producers of grain products to the requirements of European quality standards can be ensured through advanced technology and effective management decisions. It is proved that to achieve maximum efficiency in the realization of quantitative and qualitative potential of malting barley is possible only if the placement of crops is in a favourable agro-climatic zone; the use of varietal resources adapted to the conditions of the region is agreed with the final consumer - the malt enterprise; indisputable clear implementation of the elements of technology is regulated by the target direction of cultivation.Originality. Using an array of information from a significant number of farms in different regions, for the first time, a consolidated analysis of the effectiveness of the existing technology for growing malting barley in terms of quantitative and qualitative indicators, taking into account the resource provision of farms and the results of analysis of the quality of grain harvest from specialized laboratories of malt corporations, was carried out.Practical value. Analytical information, conclusions and recommendations will help farmers to optimize the technology and cost structure and significantly increase the efficiency of production of malting barley.Key words: barley, productivity, quality, technology, resource provision, efficiency.
Keywords: Key words; barley; productivity; quality; technology; resource provision; efficiency.